Emergent Pseudocapacitance of 2D Nanomaterials. Issue 13 (5th February 2018) - Yu, Xu; Yun, Sol; Yeon, Jeong Seok; Bhattacharya, Pallab; Wang, Libin; Lee, Seung Woo; Hu, Xianluo; Park, Ho Seok
Abstract: Two dimensional (2D) nanomaterials are very attractive due to their unique structural and surface features for energy storage applications. Motivated by the recent pioneering works demonstrating "the emergent pseudocapacitance of 2D nanomaterials, " the energy storage and nanoscience communities could revisit bulk layered materials though state‐of‐the‐art nanotechnology such as nanostructuring, nanoarchitecturing, and compositional control. However, no review has focused on the fundamentals, recent progress, and outlook on this new mechanism of 2D nanomaterials yet. In this study, the key aspects of emergent pseudocapacitors based on 2D nanomaterials are comprehensively reviewed, which covers the history, classification, thermodynamic and kinetic aspects, electrochemical characteristics, and design guidelines of materials for extrinsically surface redox and intercalation pseudocapacitors. The structural and compositional controls of graphene and other carbon nanosheets, transition metal oxides and hydroxides, transition metal dichalcogenides, and metal carbide/nitride on both microscopic and macroscopic levels will be particularly addressed, emphasizing the important results published since 2010. Finally, perspectives on the current impediments and future directions of this field are offered. Unlimited combinations and modifications of 2D nanomaterials can provide a rational strategy to overcome intrinsic limitations of existing materials, offering a new‐generation energy storage materials toward a high and new position in the Ragone plot. Abstract : The key aspects of emergent pseudocapacitors based on 2D nanomaterials are comprehensively reviewed, covering the history, classification, thermodynamic and kinetic aspects, electrochemical characteristics, and design guidelines. Unlimited combinations and modifications of 2D nanomaterials provide a rational strategy to overcome intrinsic limitations of existing materials, offering new‐generation energy storage materials toward a high and new position in the Ragone plot.